Dynamic Properties of First-order Equations with Large Delay - I. S. Kashchenko (Моделирование и анализ информационных систем)
The local dynamic of the first-order differential equation with large delay is studied. The method of research is based on the normal forms theory. In critical cases having infinite dimensions, special evolutional equations playing the role of normal form are built. Different cases of correlation between the order of coefficient variance from critical values and order of delay are studied.